2003
DOI: 10.1002/ddr.10281
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Activity of New Phenoxyacetic Derivatives Related to α‐Asarone with Minimal Pharmacophore Features

Abstract: Five new series of potential hypolipidemic agents 3-7 were synthesized, in order to establish the minimal pharmacophore features associated to the potent hypocholesterolemic activity of natural a-asarone (1) and synthetic clofibrate mimetic derivatives 2. The compounds were examined in hyperlipidemic male mice after oral administration of 25, 50, and 100 mg/Kg for 6 days. The isomeric series of acids and esters 3a-3c and 4a-4c were unexpectedly less active than the most simple structural isomeric compounds 5-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Unlike the isomeric compounds 8 [Cruz et al, 2003], the ortho, meta, and para ethyl-and acetylphenoxyacetic acids and esters 9-11 and 12-14, respectively, show a quite similar potency. Because of their structural simplicity and size, it is possible that their pharmacokinetic behavior and binding to the active site are not largely modified by changes in the position of the pharmacophores.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Unlike the isomeric compounds 8 [Cruz et al, 2003], the ortho, meta, and para ethyl-and acetylphenoxyacetic acids and esters 9-11 and 12-14, respectively, show a quite similar potency. Because of their structural simplicity and size, it is possible that their pharmacokinetic behavior and binding to the active site are not largely modified by changes in the position of the pharmacophores.…”
Section: Discussionmentioning
confidence: 63%
“…Compounds 9a-9c, 10a-10c, and 11a-11c proved to be more potent hypocholesterolemic agents than their analogues 8 [Cruz et al, 2003], in which a methyl group takes over the place of the side-chain of derivatives 5. Hence, this result suggests that the optimum length of the side-chain, for the best biological effect, should be of two carbon atoms, substituting the propenyl side-chain of 1.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have reported that phenoxyacetic acids and esters 6, which take advantage of some structural pharmacophoric features of both a-Asarone (1) (Chamorro et al, 1998;Díaz et al, 1993) and fibrates, displayed a significant hypocholesterolemic activity (Labarrios et al, 1999;Cruz et al, 2003;Zúñiga et al, 2005). Recently, a number of fibrate mimetic amides, which were prepared and evaluated biologically, showed a decrease of serum cholesterol and a lowering of low-density lipoprotein (LDL) cholesterol (Hernández et al, 2004).…”
Section: Introductionmentioning
confidence: 99%